PSCP, a novel reactive sulfur donor, activates Keap1-Nrf2 signaling and attenuates mitochondrial dysfunction in diabetic retinopathy - Li, Kexin; Ji, Ruiying; Chen, Youbang; Wang, Yiwen; Guo, Yiyan; Li, Xiang; Zhang, Hui; Guo, Liang; Yang, Chun-tao (Frontiers in Endocrinology, 2025)
ObjectiveDiabetic retinopathy (DR) is a leading cause of vision loss in diabetes, yet its underlying molecular drivers remain poorly defined. This study aimed to identify diabetic stress-responsive targets and explore the therapeutic potential of the reactive sulfur donor PSCP by integrating transcriptomic and functional analyses in diabetic mouse and cell models.MethodsRetinal transcriptomic datasets from type 1 and type 2 diabetic mice (GSE111465 and GSE55389) were analyzed for mitochondrial and antioxidant gene expression. In vitro, ARPE-19 retinal pigment epithelial cells were exposed to hydrogen peroxide (H2O2) or methylglyoxal (MGO) to induce oxidative and carbonyl stress. Mitochondrial function, gene expression, and antioxidant pathway activation were assessed in the presence or absence of PSCP or/and Nrf2 inhibitor ML385.ResultsTranscriptomic analysis revealed consistent dysregulation of mitochondrial antioxidant enzymes IDH2 and MGST1 in diabetic retinas. Oxidative and carbonyl stress in ARPE-19 cells led to reactive oxygen species accumulation, loss of mitochondrial membrane potential, and reduced cell viability, accompanied by suppression of IDH2 and MGST1. PSCP treatment induced Keap1 modification and promoted Nrf2 nuclear translocation, restoring the expression of IDH2, MGST1, and mitochondrial dynamics regulators MFN2 and FIS1. PSCP also preserved mitochondrial membrane potential and improved cell survival. This protective effect was abrogated by ML385.ConclusionsOur findings identify IDH2 and MGST1 as stress-responsive mitochondrial targets in DR and demonstrate that PSCP activates the Keap1-Nrf2 pathway to preserve mitochondrial integrity under diabetic stress.